Developing English Materials for Islamic Education Students of STAIN Kediri - Fitriyah, Ima (Pusat Pengembangan Bahasa IAIN Tulungagung, 2018)
English for specific academic purposes (ESAP) has grown rapidly in line with the learnersâ needs of language especially in communication skills academically. ESAP appears to rebut conventional teaching with merely emphasizing on the language structures instead of the content. In fact, what the learners learn in the classroom should meet their needs in the future professional job. Researching ESAP, the developer attempts to develop instructional materials for Islamic education students intended to troubleshoot the communication problem for undergraduate students in State Islamic Institute of Kediri or IAIN Kediri.This study is aimed to develop ESAP instructional materials with the principles of Contextual Teaching and Learning (CTL) for students of Islamic education of IAIN Kediri.This research and development is carried out in a population of 394 students being in the second semester at IAIN Kediri. A cluster random sampling is chosen as sample. There are 40 students involved in the research out of the 6 classes in the phase of obtaining information, need analysis and try out. The result of need analysis becomes the basis of how the developer composes the instructional materials with CTL principles. All the contents of the materials refer to Islamic education package into 10 units for one semester. The developer needs to ask for judgment of the materials to attain the validity of the materials involving three experts in ESAP course design, Islamic Education teacher training and expert of designing the lay out. After the tryout, the necessary revisions is made, the materials are then validated. It can be said that through the entire steps of research and development, the materials are trustworthy and appropriate to apply at Tarbiyah Faculty at IAIN Kediri.